DEV-01. QUANTITATIVE NEEDS ASSESSMENT DIFFERENCES IN THE MANAGEMENT OF CHILDREN WITH CENTRAL NERVOUS SYSTEM (CNS) CANCER IN A MIDDLE-INCOME COUNTRY AND A HIGH-INCOME COUNTRY. Issue 2 (22nd June 2018) - Fischer, Allison; Roecker, Roberto; Finlay, Jonathan; Capellano, Andrea; Osorio, Diana
Abstract: BACKGROUND: Pediatric cancer cure rates differ among high-income countries (HIC) and low-to-middle income (LMIC) countries. The World Health Organization reports 20% of LMIC have the necessary data and resources to significantly decrease the rate of mortality in their patients. We compared individual capacities of two major pediatric institutions from a HIC and LMIC caring for children with CNS cancer, the second most common type of cancer of childhood. METHODS: A quantitative-needs assessment questionnaire and key informant interviews were used to evaluate the treatment of children with CNS cancer at IOP/GRAACC/UNIFESP children's cancer center in São Paulo, Brazil and Nationwide Children's Hospital/The Ohio State University (NCH/OSU) in Columbus, OH; United States. RESULTS: Both hospitals have 24-hour pediatric oncology, nursing and pediatric intensivist coverage. Supportive care including social workers, psychologists, child life specialists, and physical/occupational/speech therapists are available at both centers. Differences included 2 part-time neuro-radiologists and 2 pathologists at IOP/GRAACC/UNIFESP, whereas 8 full-time neuro-radiologists and 12 pathologists (with 2 specially trained in neuro-pathology) at NCH/OSU. There are 4 pediatric neurosurgeons on staff at each hospital, however, 2 surgical days at IOP/GRAACC/UNIFESP, compared to 7 days/week at NCH/OSU. Additionally, delays in initiation of radiation treatment at IOP/GRAACC/UNIFESP extended 2–4 weeks compared to less than 1 week at NCH/OSU. CONCLUSION: Center-specific differences in resources exist in highly-specialized hospitals caring for children with CNS cancer in LMIC and HIC. This quantitative-needs assessment can develop targeted strategies for effective interventions to improve on the management of children with CNS cancers.